STUDI PENGGUNAAN ALAT EVALUASI PADA MATA PELAJARAN EKONOMI MATERI AKUNTANSI KELAS XI IPS DI SMA NEGERI 22 SURABAYA - SIMON PAMUNGKAS (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2013)
This research aims to know the types of evaluation tools in SMA Negeri Surabaya teachers and 22 reasons for selecting the evaluation tool, and find out the feasibility of the evaluation tools used. This research is descriptive research type with quantitative approach. The results showed that the evaluation tools used in SMA Negeri 22 Surabaya is kind of a test, such as a written Test and an oral Test. From the results of the study the evaluation tool experts retrieved the results that the evaluation tools used in SMA Negeri 22 Surabaya has a very worthy category Keyword: evaluation, accounting, social science , high school